Respuesta :
Answer:
C) 5,-1
Step-by-step explanation:
Given equation is [tex]\[x^{2}-4x=5\][/tex]
Expressing the equation equivalently,
[tex]\[x^{2}-4x-5=0\][/tex]
[tex]\[=> x^{2}-5x+x-5=0\][/tex]
[tex]\[=> x*(x-5)+1*(x-5)=0\][/tex]
[tex]\[=> (x-5)*(x+1)=0\][/tex]
Hence the solutions of this equation can be represented as x-5=0 and x+1=0
In other words, x=5 or x=-1
Among the given options, option C is the correct one.
Answer:
C
Step-by-step explanation:
Step 1, the coefficient of x is -4
Step 2, divide it by 2= -2
Step 3, square your answer and add to both sides
Square of -2 is 4, and we add to both sides of the equation to give,
x^2 - 4x + 4 = 5 +4
X^2 +4 = 9
(x +2)^2 = 9
take the sqrt of both sides, we have
X +2 = sqrt (9)
X = 2(+ or -) Sqrt (9)
X = 2+ Sqrt (9), 2-sqrt (9)
X = 2+3, 2-3
X= 5, -1